Local subdifferentials and multivariational inequalities in Banach and Frechet spaces - Pavlo O. Kasyanov (Opuscula Mathematica, 2008)
Some functional-topological concepts of subdifferential and locally subdifferential maps in Frechet spaces are established. Multivariational inequalities with an operator of the pseudo-monotone type, connected with subdifferential maps, are considered.